TINDAKAN NEGARA TERKAIT PERISTIWA G30S: STUDI MAKNA GADAMERIAN PADA PESELAMAT - Atmaja, Hamdan Tri (History Department, Semarang State University and Historian Society of Indonesia, 2012)
This study aims to gain knowledge of a deep understanding of the state action related to the G30S event. The research method used was a qualitative research approach initiated by Gadamer's hermeneutics. The results showed that state action against survivors were to arrest, investigate, and imprison them to the island of Buru (for men survivors) and Plantungan (for women survivors). The G30S event, by survivors, was interpreted as a story of the assassination of the generals by Indonesian Communist Party (PKI), as well as the form of a political conspiracy for SukarnoÃ¢â‚¬â„¢s power within ideological background. Investigation and arrest were interpreted by them as an act of unwarranted, political scapegoat, and a form of abuse against them. While prison life, for survivors, was as a form of forced labor, punishment to stigmatize and isolate women Keywords: State Action, the G30S event, Meaning, and Survivor. Ã‚Â Tulisan ini mendeskripsikan secara mendalam tindakan negara terkait peristiwa G30S. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan hermeneutika yang digagas Gadamer. Hasil penelitian menunjukkan tindakan negara terhadap peselamat adalah melakukan penangkapan, pemeriksaan, dan penahanan serta memenjarakan mereka ke pulau Buru (untuk peselamat laki-laki) dan Plantungan (untuk peselamat perempuan). Peristiwa G30S oleh peselamat dimaknai sebagai kisah pembunuhan para jendral oleh PKI, bentuk konspirasi politik memperebutkan kekuasaan Soekarno dengan latar belakang ideologi. Pemeriksaan dan penangkapan dimaknai peselamat sebagai tindakan tidak beralasan, politik kambing hitam, dan sebagai bentuk kesewenang-wenangan terhadap peselamat. Kehidupan penjara dimaknai peselamat sebagai bentuk kerja paksa, hukuman dengan menstigmatisasi dan mengisolasi kaum perempuan. Kata kunci: Tindakan Negara, Peristiwa G30S, Makna, danÃ‚Â Peselamat. Ã‚Â Ã‚Â Ã‚Â